2021
DOI: 10.18240/ijo.2021.06.21
|View full text |Cite
|
Sign up to set email alerts
|

Primary rhegmatogenous retinal detachment: evaluation of a minimally restricted face-down positioning after pars plana vitrectomy and gas tamponade

Abstract: AIM: To evaluate the safety and efficacy of a minimally restricted face-down postoperative positioning following pars plana vitrectomy (PPV) with gas tamponade for primary rhegmatogenous retinal detachment (RRD). METHODS: Patients with primary RRD treated with PPV and gas tamponade and followed up for at least 6mo were selected for the study. All phakic eyes underwent simultaneous cataract surgery. The patients were required to be in a postoperative position that prevented downward flow of retinal tears. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Patients' demographics data are summarized in Table 1. Patients with previous vitreoretinal surgery history, penetrating injury, uveitis, aphakia, age-related macular degeneration, diabetic retinopathy, or uncontrolled glaucoma were excluded [15][16] . After eye anesthesia, standard 23-G vitrectomy was performed through the flat part of ciliary body, the perfusion catheter was closed, and the vitreous in the central axis was excised.…”
Section: Subjects and Methods Ethical Approvalmentioning
confidence: 99%
“…Patients' demographics data are summarized in Table 1. Patients with previous vitreoretinal surgery history, penetrating injury, uveitis, aphakia, age-related macular degeneration, diabetic retinopathy, or uncontrolled glaucoma were excluded [15][16] . After eye anesthesia, standard 23-G vitrectomy was performed through the flat part of ciliary body, the perfusion catheter was closed, and the vitreous in the central axis was excised.…”
Section: Subjects and Methods Ethical Approvalmentioning
confidence: 99%
“…The single-surgery anatomic success rates for rhegmatogenous retinal detachment (RRD) repair using standard treatment methods have historically been over 90%. [1][2][3][4][5][6][7][8][9] Primary pars plana vitrectomy (PPV) with endolaser application and postoperative intraocular gas tamponade has continued to increase in popularity as the preferred treatment for uncomplicated RRD because of excellent single-surgery anatomic success rates and decreased patient discomfort. [1][2][3][4][5]10 Although such studies sought to elucidate the efficacy of primary PPV in the setting of RRD, there is less discussion on how postoperative prone positioning, especially the lack thereof, affects single-surgery anatomic success rates and visual outcomes for RRD patients in the modern microincision vitrectomy surgery (MIVS) era.…”
Section: Introductionmentioning
confidence: 99%
“…1,11 Since then, MIVS has evolved into the most common surgical intervention for RRD repair with the addition of endolaser application and intraocular gas tamponade (eg, 20% sulfur hexafluoride [SF 6 ]; 14% perfluoropropane [C 3 F 8 ]) with strict postoperative face-down positioning. [1][2][3][4][5][6][7][8]10 These adaptations have improved the rate of successful primary vitrectomy for RRD to approximately 90%, [1][2][3][4]8,10 with facedown positioning lasting between 7 days and 14 days. 1,3,4 Still, maintaining face-down positioning is a major complaint of patients having vitreoretinal surgery and is associated with poor patient compliance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…M aintaining a specific head position during the postoperative period after pars plana vitrectomy (PPV) is usually recommended following retinal surgical procedures, such as repair of rhegmatogenous retinal detachment (RD) and full-thickness macular hole. 1,2 Although there is no consensus regarding the necessity of maintaining face-down position, 3 a survey of retinal specialists in 2020 indicated that 86.7% of surgeons in the United States instruct their patients to position face down for more than one day after macular hole surgery. 4 Prior work has demonstrated that after macula-involving RD repair, face-down positioning is associated with a reduction in the rate and amplitude of postoperative retinal displacement and reduction in binocular diplopia.…”
mentioning
confidence: 99%